Ledarskap, kommunikation och målsättning som motivationsfaktorer : en fallstudie på Fresenius Kabi i Uppsala - Bolinder, Lisa (SLU/Dept. of Economics, 2010)
It's not a secret that most companies strive to get such a high economic return as possible. To successfully engage in a profitable enterprise, there are many elements that come into play. An important element is the motivation of the employees and their work performance. Work motivation is a key factor for the employees to improve their performance and therefore determinant for the successes of the company.